Human rights approach to disability in the Maldivian legal framework - Shiuny, Fathimath (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2016)
Disability and human rights are among the foremost concerns of international community. Towards the end of twentieth century, the linkages between the protection of human rights and disability began to manifest. Since then, there has been increasing awareness and acknowledgement of the correlation between the two subjects. The poor conditions of the persons with disabilities in the Maldives has led to the incidences of human rights violations notwithstanding the adoption of human rights treaties and fundamental human rights in the Maldives Constitution. This has led to the violation of the rights to life, right to health, right to accessibility to physical environment, information, transport facilities, right to education, right to work and employment and right to development and participation. Therefore, this thesis examines the relationship between human rights and disability as an attempt to show the indivisibility of the two fields. It seeks to discover how deteriorating condition of disability affects the enjoyment of basic human rights to the people of Maldives. The research work also assesses the effectiveness or otherwise of the legal framework on disability rights protection in Maldives. This is done through the examination of the constitutional status on disability rights, National Policy on Disability and Disability Act. Also, the thesis examines the position of Islamic Law on the rights of persons with disabilities. This was done through the examination of the rights provided for persons with disabilities in Islam such as right to honour and dignity, right to accessibility, right to education, right to work, right to medical treatment and right to financial assistance. The thesis primarily adopts qualitative method of research, which involves both doctrinal and non-doctrinal legal research. On this note, the research work finds the existing law on disability rights protection in Maldives to be weak and insufficient and this underscores the unsatisfactory performance of the regulatory bodies. As a result of these findings, the research work suggests some recommendations in order to reinforce the legal frameworks and improve civil rights justice. Also, important recommendations are made to the government so as to promote and protect human rights of persons with disabilities.